2020
DOI: 10.1097/md.0000000000019899
|View full text |Cite
|
Sign up to set email alerts
|

Full recovery of near complete tear of anterior cruciate ligament without surgery: a case report

Abstract: Introduction: The anterior cruciate ligament (ACL) is the region where spraining or tearing is most prevalent when the knee is injured. Complete ACL ruptures have a much less favorable outcome without surgical intervention. Polydeoxyribonucleotide (PDRN) is a relatively safe substance widely used for regenerative therapy. Patient concerns: A 43-year-old female patient visited our clinic with Rt. knee pain after slipping, which she rated as 7/10 on a numeric rating scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In contrast data about spontaneous healing of an ACL rupture is lacking. Only some sample studies reported the possibility of healing of a ruptured ACL [ 17 , 18 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast data about spontaneous healing of an ACL rupture is lacking. Only some sample studies reported the possibility of healing of a ruptured ACL [ 17 , 18 , 40 ].…”
Section: Discussionmentioning
confidence: 99%